Pengaruh Persepsi Harga dan Brand Awareness terhadap Keputusan Pembelian Sabun Mandi Merek Lifebuoy - Mulyani, Sri; Murni, Yanti; Putri, Maharani (Jurnal Informatika Ekonomi Bisnis, 2024)
The data analysis technique used is multiple linear regression analysis. Based on the research results, it was obtained that the multiple linear equation Y= 6.554 + 0.538X1+ 0.306X2. Based on the results of the t test, the price perception variable (X1) has a positive and significant effect on the decision to purchase Lifebuoy brand bath soap (5.688 > 1.66298) with a significance level of 0.000 (0.000 1.66298) with a significance level of 0.010 (0.010 3.11) with a significant level (0.000 < 0.05), it can be stated that price perception (X1) and brand awareness (X2) simultaneously have a positive and significant effect on soap purchasing decisions. Lifebuoy brand bath in Nagari Koto Dalam Barat, Padang Sago District. The magnitude of the influence of price perception and brand awareness on the decision to purchase Lifebuoy bath soap is 52.7%, while the remaining 47.3% is influenced by other than the model studied.